Research and application of macro-micro fracture correlation of heterogeneous granite - Chen, Yunjuan; Su, Jiarui; Gao, Tao; Jing, Yi; Zhang, Huifu; Duan, Hongjie; Zhao, Wenbin (Frontiers in Earth Science, 2024)
Granite structure has the characteristics of discrete distribution and random distribution of minerals, which is particularly critical to the stability of surrounding rock of underground caverns, and the research process is extremely complicated. In this paper, the granite of Dagangshan tunnel in rock sections of class Ⅲ was taken as the research object, and the mineral composition and proportion, the macro and micro characteristics of granite was analyzed by XRD analysis, SEM and laboratory compressive test; Dagangshan tunnel’s section model with surrounding rock of class Ⅲ was established using the particle flow program PFC and the numerical simulation was done, thus the influence of micro composition and proportion on surrounding rock masses’ stability with the tunnel excavation was analyzed. Results show that: The content of illite and albite is the most, and illite is the weak mineral of the granite. for the granite of Dagangshan tunnel with rock masses of class Ⅲ, the rock failure is mainly caused by shear force and secondary by tensile force. Fracture is mainly concentrated in the enrichment area of “weakened minerals”, where as the breakthrough point and expands to other parts, and further connects. The “enhanced minerals” are basically stable because of their high hardness and strong link between each other. After tunnel excavation, cracks of tunnel’s side walls and the arch foots are more serious, so the supporting measures of these parts should be strengthened.